PERSPEKTIF PENERAPAN PENGENDALIAN HAMA TERPADU DALAM USAHATANI LADA - HENDAYANA, RACHMAT; DERMOREDJO, SAKTYANU K.; NURASA, TJETJEP; ELIZABETH, ROOSGANDHA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 2 Juli 2006)
The research conducted in Bangka Belitung and Lampung in FY 2003, with PRA approach through group discussion technique. This research aims to identify the performance, problems and implementation perspective of Integrated Pest Management (IPM) in pepper farming system and also to identify socio-economic factors influencing IPM adoption. Through qualitative and quantitative descriptive analysis, shows: (a) Introduction of IPM principle not yet entirely adopted by farmer of Field Laboratory-IPM participant; (b) Influencing factors of IPM adoption are covering internal and external factors having the character of technical and non technical namely farmer characteristic, owner of farm status, accessibilities of farming system location and market of input, pepper price, and also continuity of counseling by extension agent of agriculture; (c) Practically farmer did not get added value of IPM adoption because pepper farmer was sold in form of unsorted product, (d) Reorientation for training curriculum of IPM in FL-IPM and also intensive guidance to encourage farmer in carrying out of IPM is needed.
Keywords: Pepper, Integrated Pest Management, Perspective, Bangka Belitung, Lampung